Web portal systems for managing a supercomputer - Korzh, A.A.; Golovynskyi, A.L.; Malenko, A.L.; Belous, L.F. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2010)
At present, the user access to computing resources requires a fairly deep knowledge of many technical details in addition to the properties of parallel software packages and their specific languages. The progress of grid technologies did not simplified the situation, but did it more complex by adding a requirement of ability to work in the command line mode in the Unix operating environment. On the other hand, the problem of administration of a computing cluster is a difficult and time-consuming activity. This paper is an attempt to propose a solution to both the problems. The authors offer an integrated solution in the form of a web portal system for managing a cluster, which allows the users to control the passage of their tasks without the necessity to study many details of supercomputer operational environment. A convenient service including the console mode have been designed to manage a cluster. This project is implemented and used successfully in leading supercomputing centers of Ukraine.